2013
DOI: 10.1371/journal.pone.0065741
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Targeted Mechanisms Underlying the Endothelial Protective Effects of the Diabetic-Safe Sweetener Erythritol

Abstract: Diabetes is characterized by hyperglycemia and development of vascular pathology. Endothelial cell dysfunction is a starting point for pathogenesis of vascular complications in diabetes. We previously showed the polyol erythritol to be a hydroxyl radical scavenger preventing endothelial cell dysfunction onset in diabetic rats. To unravel mechanisms, other than scavenging of radicals, by which erythritol mediates this protective effect, we evaluated effects of erythritol in endothelial cells exposed to normal (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 55 publications
1
17
1
Order By: Relevance
“…In contrast to prior animal studies [2,3], there were no effects of erythritol on markers of oxidative stress and inflammation. These findings might reflect the modest sample size, short duration of treatment, lower relative dose of erythritol, and a lack of correlation between these systemic measures and local effects in the vascular wall.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to prior animal studies [2,3], there were no effects of erythritol on markers of oxidative stress and inflammation. These findings might reflect the modest sample size, short duration of treatment, lower relative dose of erythritol, and a lack of correlation between these systemic measures and local effects in the vascular wall.…”
Section: Discussioncontrasting
confidence: 99%
“…In vitro studies suggest that erythritol reduces stress-induced endothelial apoptosis and alters the transcription of genes relevant to mitochondrial function, antioxidant protection, and cell signaling [3]. The present study provides novel information about the relevance of that experimental work to humans.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…It can also improve mouthfeel and mask certain unwanted aftertastes of intense sweeteners [23]. Erythritol was also reported to protect endothelial cells under hyperglycemic conditions (Table 4) [28]. In vitro studies have also shown that erythritol is an excellent radical scavenger with membrane-protecting properties [19,23].…”
Section: Lactitolmentioning
confidence: 99%
“…Diabetes patients can benefit from the vascular effects of erythritol, as mentioned above. It is assumed that endothelium is not compromised by erythritol in non-diabetic subjects, but in diabetic subjects where endothelium is under diabetic stress, erythritol can transfer a range of damage and dysfunction parameters to a safer side, as in vitro , ex vivo and in vivo studies report [ 148 , 150 , 151 ]. Erythritol can also be regarded as a substance with a beneficial impact on the endothelium under high-glucose conditions by contributing to avoid or delay the onset of diabetic complications [ 152 ].…”
Section: Health Impactsmentioning
confidence: 99%